High-resistivity NdFeB permanent magnet material and high-flux preparation method thereof
Through high-throughput experimental methods and thermal isostatic pressure treatment, a high-resistivity NdFeB permanent magnet material was prepared, which solved the problem of degradation of magnetic properties of NdFeB permanent magnet material in high-temperature environments, and improved the material without increasing costs. resistivity.
Patent Information
- Application Number
- CN202411567863.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-05
AI Technical Summary
The existing NdFeB permanent magnet materials are prone to thermal demagnetization under high temperature environments, resulting in a decrease in magnetic properties. The commonly used methods for adding heavy rare earth elements increase costs, and traditional methods are difficult to improve resistivity without losing magnetic properties.
The multi-sections are prepared by high-throughput experimental methods, and the interface is closely linked through thermal isostatic pressure treatment, and the reasonable diffusion layer components are designed to allow heavy rare earths to diffuse into the main phase to form a core-shell structure, thereby enhancing the wettability and resistance of the grain boundary phase Rate.
Without losing magnetic properties, the resistivity of NdFeB permanent magnet material is significantly improved, the problem of thermal demagnetization in high temperature environments is solved, and the R&D cost is reduced.
Smart Images

Figure CN119400536A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of rare earth permanent magnets, and in particular to a high-resistivity NdFeB permanent magnet material and a high-throughput preparation method thereof. Background Art
[0002] As the social energy structure continues to be optimized, the demand for permanent magnet materials in low-carbon economic fields such as energy-saving home appliances, new energy vehicles and wind power generation will also increase significantly. Permanent magnet motors are more popular in the market than excitation motors due to their high efficiency, low energy consumption, good stability, and advantages in weight and volume. With the rapid development of the low-carbon economy and the increasing application scenarios, the market has put forward higher performance requirements for permanent magnet motors, and there is an urgent need to develop safer, more reliable and efficient permanent magnet motors.
[0003] The preferred permanent magnet for permanent magnet motors is NdFeB permanent magnet. The operating environment temperature of permanent magnet synchronous traction motors for new energy vehicles and permanent magnet synchronous generators for wind turbines is often as high as 150°C or even 250°C. However, due to the low Curie temperature of NdFeB magnets (about 312°C), conventional NdFeB magnets are prone to thermal demagnetization in such high temperature environments, resulting in a decrease in their magnetic properties and the inability to ensure the efficient operation of permanent magnet motors. At present, the method of adding expensive and scarce heavy rare earth elements such as Dy and Tb is often used to increase its coercive force, resulting in a significant increase in cost. The rotor temperature can also be reduced by adding water cooling devices, but this will limit the structural design of the motor and cannot fundamentally solve the material problem.
[0004] The heat generated by the rotor is mainly determined by its resistivity. By introducing high-resistivity scattering elements into NdFeB, the scattering rate of electrons can be increased, which can reduce the heat generation. Most of the current research introduces insulating oxide particles containing Si, Zn and Sn to increase the resistivity, which is bound to lead to a significant decrease in magnetic properties. The grain boundary diffusion method is used to form a continuous rare earth oxide grain boundary phase along the main phase boundary layer, which can improve the resistivity while ensuring the coercive force. Therefore, the grain boundary diffusion method is an optional method for the research and preparation of high-resistivity NdFeB permanent magnet materials. However, the grain boundary diffusion method relies on a large number of experiments, and it is necessary to explore suitable diffusion substrates and diffusion source components, and explore the optimal diffusion process, in order to obtain high-resistivity NdFeB permanent magnet materials that meet the needs of practical applications. This process requires a lot of manpower, material resources, and financial resources, which greatly limits the research and development of high-resistivity NdFeB permanent magnet materials. Summary of the invention
[0005] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a high-resistivity NdFeB permanent magnet material and a high-throughput preparation method thereof. The present invention adopts a high-throughput experimental method, and obtains a large number of parallel samples in a short time by preparing a multi-node. Combined with a high-throughput test characterization method, the experimental efficiency can be effectively improved. The method of diffusion multi-node is adopted, and the interface is tightly combined by applying hot isostatic pressing, so that higher mechanical properties can be obtained. Through the reasonable design of the diffusion layer composition, the heavy rare earth is diffused into the main phase to form a core-shell structure, the wettability and resistivity of the grain boundary phase are improved, and then the overall resistivity is improved without losing magnetic properties.
[0006] The high-throughput preparation method of the high-resistivity NdFeB permanent magnetic material provided by the present invention comprises the following steps:
[0007] (1) preparing an oblong sleeve with a length, width and height of l*m*n and a cover with a length, width and height of l*m*k, and processing a rectangular groove in the sleeve;
[0008] (2) preparing a magnet bar M with a length, width and height of a*b*d, preparing a diffusion source bar T with a length, width and height of a*c*d, and grinding and polishing the surface; where in millimeters, 10≥a≥3, 10≥b≥3, c≥0.5, d≥3;
[0009] (3) Alternately assembling the magnet bars and the diffusion source bars into the rectangular slots, covering them with lids, and performing vacuum electron beam welding;
[0010] (4) subjecting the welded package to hot isostatic pressing to obtain a diffusion multi-element node;
[0011] (5) cutting the diffusion multi-node into multiple slices parallel to the long elliptical surface, sealing the tube and performing diffusion heat treatment at different temperatures or times according to subsequent test requirements to obtain multiple groups of high resistivity NdFeB permanent magnet material diffusion multi-nodes under different heat treatment conditions;
[0012] (6) Conduct resistivity and magnetic property tests on each interface of the obtained NdFeB permanent magnet material diffusion multi-node, and select the interface that meets the required resistivity and magnetic property requirements; according to the component composition on both sides of the interface and the corresponding heat treatment conditions, a high resistivity NdFeB permanent magnet material with the required performance can be prepared. The resistivity and magnetic property requirements are determined according to the subsequent application requirements. After obtaining the component composition on both sides of the interface, the magnet component and diffusion source component of the corresponding components can be selected, and the treatment is carried out according to the powder metallurgy preparation process and the corresponding heat treatment conditions known in the art.
[0013] Furthermore, in step (1), the sheath material is one of 304 stainless steel, pure iron, and Cr metal.
[0014] Furthermore, the magnet strip M in step (2) can be selected from one or more of NdFeB magnets and NdDyTbFeB magnets, wherein the composition of the NdFeB magnet is: (Nd x Pr y A z D 1-x-y-z ) a Fe bal M c B e , Nd is the rare earth element neodymium, Pr is the rare earth element praseodymium, A is one or more rare earth elements La, Ce, Y, D is one or more rare earth elements other than Dy, Tb, Nd, Pr, La, Ce, Y, Fe is iron, B is boron, M is one or more elements of Al, Ga, Cu, Ti, Cr, Mn, Mo, Nb, P, Si, Ta, V, Zr, Ni, Co; wherein the composition of NdDyTbFeB magnet is: (Nd x’ Pr y’ R z’ E 1-x’-y’-z’ ) b Fe bal N d B f , R is one or two of the rare earth elements Dy and Tb, E is one or more of the rare earth elements other than Dy, Tb, Nd, Pr, La, Ce, and Y, and N is one or more of the elements selected from Al, Ga, Cu, Ti, Cr, Mn, Mo, Nb, P, Si, Ta, V, Zr, Ni, and Co; calculated by mass percentage, 0.2≤x≤1, 0≤y≤0.5, 0≤z≤0.8, 28.5≤a≤33.5, 0.3≤c≤6, 0.85≤e≤1.5, 0.5≤x'≤1, 0≤y'≤0.4, 0.05≤z'≤0.5, 27≤b≤33.5, 0.2≤d≤6, 0.85≤f≤1.5, and bal means that the rest is Fe after removing other elements.
[0015] Furthermore, the diffusion source strip T in step (2) can be selected from S g Fe bal Q h S t One or more of the following: S is one or more rare earth elements Dy, Tb, Nd, Pr, Gd, and Ho, Fe is iron, Q is one or more elements selected from Al, Ga, Cu, Ni, and Co; S is one or more elements selected from Sn, Si, Zn, Zr, and Pb; 0.5≤g≤0.8, 0.05≤h≤0.45, and 0.05≤t≤0.45 are satisfied; bal means that all that remains after removing other elements is Fe.
[0016] When there are multiple magnet bars M or diffusion source bars T with different compositions, the principle of staggered arrangement of magnet bars M and diffusion source bars T is still followed, that is, no matter whether the composition of magnet bars M is the same or different, two magnet bars M need to be separated by a diffusion source bar T, and similarly, two diffusion source bars T also need to be separated by a magnet bar M.
[0017] Furthermore, the vacuum degree of the vacuum electron beam welding in step (3) is 5*10 -5 ~5*10 -4 Pa, weld width is 0.5~1.5mm.
[0018] Furthermore, the hot isostatic pressing treatment temperature in step (4) is 650-1000° C., the time is 2-5 hours, and the pressure is 50-300 MPa.
[0019] Furthermore, the sealing tube in step (5) is an argon atmosphere of 0.03-0.06 MPa. Furthermore, the diffusion heat treatment time in step (5) is 2-30 days, and the diffusion heat treatment temperature is 800-1100°C.
[0020] The present invention further provides a NdFeB permanent magnet material prepared by the method. The composition and heat treatment conditions of the NdFeB permanent magnet material that meets the requirements of high resistivity and magnetic properties can be quickly determined by the method of the present invention.
[0021] The beneficial effects of the present invention compared with the prior art are as follows:
[0022] 1) The present invention prepares diffusion multi-nodes of different components, quickly grasps the influence of diffusion sources of different systems on the resistivity of permanent magnets, and efficiently prepares permanent magnet materials with high magnetic properties and high resistivity.
[0023] 2) The present invention uses different heat treatment temperatures and times to quickly grasp the diffusion thermodynamics of the diffusion source in the magnet at different temperatures and efficiently screen the appropriate heat treatment process.
[0024] 3) The present invention adopts a high-throughput experimental method, a large number of samples can be obtained through one experiment, and a large amount of data can be obtained through centralized parallel testing and characterization. Compared with the traditional experimental trial and error method, the research and development efficiency of high resistivity permanent magnetic materials can be greatly improved.
[0025] 4) The prepared multi-node forms a Dy / Tb-rich shell layer in the main phase of the magnet through heat treatment to improve the coercive force; at the same time, a continuous and high-resistivity grain boundary phase (mainly rich in rare earth compounds) is formed to improve the overall resistivity of the magnet. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Schematic diagram of the diffused multi-node arrangement of high resistivity permanent magnetic materials. DETAILED DESCRIPTION
[0027] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments:
[0028] Embodiment 1:
[0029] (1) Preparation size is 30*18*45mm 3 The long oval package and the size is 30*18*1mm 3 The cover is processed into a 21*13*40mm long oval sleeve. 3 Rectangular groove; the sheath material is 304 stainless steel;
[0030] (2) Preparation size is 21*2.5*40mm 3 Nd 0.65 Pr 0.15 Ce 0.2 ) 30 Fe bal Al 0.2 Ga 0.5 Nb 0.2 B1 magnet strip, 21*1*40mm 3 Nd 0.6 Cu 0.25 Sn 0.1 Si 0.05 、Nd 0.6 Cu 0.25 Sn 0.15 、Nd 0.6 Cu 0.35 Si 0.05 Diffusion source strip, surface sandpaper grinding and polishing machine polishing;
[0031] (3) Alternately assemble four magnet bars and three diffusion source bars into the rectangular slots (two magnet bars are separated by a diffusion source bar, and two diffusion source bars are separated by a magnet bar, such as Figure 1 As shown), cover the lid and perform vacuum electron beam welding; the vacuum degree of vacuum electron beam welding is 5*10 -4 Pa, weld width is 0.5 mm;
[0032] (4) The welded package is subjected to hot isostatic pressing to obtain a diffusion multi-node; the hot isostatic pressing temperature is 750°C, the time is 4 hours, and the pressure is 200 MPa;
[0033] (5) The multi-node was cut into 8 slices parallel to the long elliptical surface, and the slices were sealed. After sealing, they were evenly divided into 4 temperature groups (two slices in each group), and diffusion heat treatments were performed at four different temperatures of 800°C, 900°C, 1000°C, and 1100°C. The diffusion heat treatment time of the two slices in each group was 7 days and 15 days, respectively. Eight high-resistivity NdFeB permanent magnet materials were obtained, and their partial resistivities are shown in Table 1 below. Since the composition of the magnet bars is the same, the diffusion source is used to represent each interface in Table 1.
[0034] (6) Based on the comprehensive consideration of composition, corresponding resistivity and magnetic properties, (Nd 0.65 Pr 0.15 Ce 0.2 ) 30 Fe bal Al 0.2 Ga 0.5 Nb 0.2 B1 / Nd 0.6 Cu 0.25 Sn 0.1 Si 0.05 Interface, heat treatment temperature 900℃, time 15 days, through (Nd 0.65 Pr 0.15 Ce 0.2 ) 30 Fe bal Al 0.2 Ga 0.5 Nb 0.2 Addition of Nd to B1 0.6 Cu 0.25 Sn 0.1 Si 0.05 , a high resistivity sintered permanent magnet is obtained.
[0035] Table 1
[0036] Diffusion source Temperature / ℃ Time / Day Interface resistivity / μΩ·cm <![CDATA[Nd 0.6 With 0.25 Sn 0.1 And 0.05 ]]> 800 7 1003 <![CDATA[Nd 0.6 With 0.25 Sn 0.1 And 0.05 ]]> 800 15 1218 <![CDATA[Nd 0.6 With 0.25 Sn 0.1 And 0.05 ]]> 900 7 7309 <![CDATA[Nd 0.6 With 0.25 Sn 0.1 And 0.05 ]]> 900 15 8215 <![CDATA[Nd 0.6 With 0.25 Sn 0.15 ]]> 900 7 8012 <![CDATA[Nd 0.6 With 0.35 And 0.05 ]]> 900 15 6547
[0037] Embodiment 2:
[0038] (1) Preparation size is 32*20*51mm 3 The long oval package and the size is 32*20*1mm 3 The cover is processed into a 24*17*45mm long oval cover. 3 Rectangular groove; the sheath material is 304 stainless steel;
[0039] (2) Preparation size is 24*3.5*45mm 3 (Nd 0.85 Pr 0.1 Dy 0.05 ) 30.5 Fe bal Al0.15 Ga 0.45 Co 0.2 Zr 0.15 B 0.95 Magnet bar, 24*1*45mm 3 Nd 0.6 Tb 0.1 Fe 0.1 Cu 0.15 Si 0.05 、Nd 0.55 Tb 0.1 Fe 0.1 Cu 0.15 Si 0.1 、Nd 0.5 Tb 0.1 Fe 0.1 Cu 0.15 Si 0.15 Diffusion source strip, surface sandpaper grinding and polishing machine polishing;
[0040] (3) Alternately assemble four magnet bars and three diffusion source bars into the rectangular slots (two magnet bars are separated by a diffusion source bar, and two diffusion source bars are separated by a magnet bar, such as Figure 1 As shown), cover the lid and perform vacuum electron beam welding; the vacuum degree of vacuum electron beam welding is 5*10 -5 Pa, weld width is 1.5 mm;
[0041] (4) The welded package is subjected to hot isostatic pressing to obtain a diffusion multi-node; the hot isostatic pressing temperature is 650°C, the time is 2h, and the pressure is 50MPa;
[0042] (5) The multi-node was cut into 10 slices parallel to the long elliptical surface, and the slices were sealed. After sealing, they were evenly divided into 5 temperature groups (two slices in each group), and diffusion heat treatments were performed at five different temperatures of 900°C, 950°C, 1000°C, 1050°C, and 1100°C. The diffusion heat treatment time of the two slices in each group was 7 days and 15 days, respectively. The cooling method was quenching, and 10 high resistivity NdFeB permanent magnet materials were obtained. Some of their resistivity test results are shown in Table 2 below. Since the composition of the magnet bars is the same, the diffusion source is used to represent each interface in Table 2.
[0043] (6) Based on the comprehensive consideration of composition, corresponding resistivity and magnetic properties, (Nd 0.85 Pr 0.1 Dy 0.05 ) 30.5 Fe bal Al 0.15 Ga 0.45 Co 0.2 Zr 0.15 B 0.95 / Nd 0.55 Tb 0.1 Fe 0.1 Cu 0.15 Si 0.1 Interface, heat treatment temperature 1050℃, time 7 days, by (Nd 0.85 Pr 0.1 Dy 0.05 ) 30.5 Fe bal Al 0.15 Ga 0.45 Co 0.2 Zr 0.15 B 0.95 Add Nd 0.55 Tb 0.1 Fe 0.1 Cu 0.15 Si 0.1 , a high resistivity sintered permanent magnet is obtained.
[0044] Table 2
[0045]
[0046] Embodiment 3:
[0047] (1) Preparation size is 32*20*51mm 3 The long oval package and the size is 32*20*1mm 3 The cover is processed into a 24*17*45mm long oval cover. 3 Rectangular groove; the sheath material is 304 stainless steel;
[0048] (2) Preparation size is 24*3.5*45mm 3 Nd 0.8 Pr 0.1 Dy 0.1 ) 30.5 Fe bal Cu 0.25 Al 0.25 Ga 0.5 Co 0.5 Ti 0. 2B 0.95 、(Nd 0.65 Pr 0.15 Dy 0.2 ) 30.5 Fe bal Al 0.15 Ga 0.5 Co 0.6 Ti 0.3 B 0.92 、(Nd 0.75 Pr 0.1 Dy 0.15) 31 Fe bal Al 0.25 Ga 0.35 Nb 0.2 B1、(Nd 0.6 Pr 0.1 Dy 0.3 ) 31.5 Fe bal Cu 0.25 Al 0.25 Ga 0.35 Co 0.5 Ti 0.25 B 0.98 Magnet bar, 24*1*45mm 3 Nd 0.5 Zn 0.39 Sn 0.06 Cu 0.025 Al 0.025 Diffusion source strip, surface sandpaper grinding and polishing machine polishing;
[0049] (3) Alternately assemble four magnet bars and three diffusion source bars into the rectangular slots (two magnet bars are separated by a diffusion source bar, and two diffusion source bars are separated by a magnet bar, such as Figure 1 As shown), cover the lid and perform vacuum electron beam welding; the vacuum degree of vacuum electron beam welding is 5*10 -5 Pa, weld width is 1 mm;
[0050] (4) The welded package is subjected to hot isostatic pressing to obtain a diffusion multi-node; the hot isostatic pressing temperature is 650°C, the time is 2h, and the pressure is 50MPa;
[0051] (5) The multi-node was cut into 10 slices parallel to the long elliptical surface, and the slices were sealed. After sealing, they were divided into 5 temperature groups (two slices in each group), and diffusion heat treatments were carried out at five different temperatures of 900°C, 950°C, 1000°C, 1050°C, and 1100°C. The diffusion heat treatment time of the two slices in each group was 5 days and 10 days, respectively. The cooling method was quenching, and 10 high resistivity NdFeB permanent magnet materials were obtained. Some of the resistivity test results are shown in Table 3 below. Since the composition of the diffusion strips is the same, the interfaces in Table 3 are represented by magnets.
[0052] (6) Based on the comprehensive consideration of composition, corresponding resistivity and magnetic properties, (Nd 0.65 Pr 0.15 Dy 0.2 ) 30.5 Fe bal Al 0.15 Ga 0.5 Co 0.6 Ti0.3 B 0.92 / Nd 0.5 Zn 0.39 Sn 0.06 Cu 0.025 Al 0.025 Interface, heat treatment temperature 1050 ℃, time 5 days, by (Nd 0.65 Pr 0.15 Dy 0.2 ) 30.5 Fe bal Al 0.15 Ga 0.5 Co 0.6 Ti 0.3 B 0.92 Add Nd 0.5 Zn 0.39 Sn 0.06 Cu 0.025 Al 0.025 , a high resistivity sintered permanent magnet is obtained.
[0053] Table 3
[0054]
[0055] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the attached claims.
Claims
1. A high-throughput preparation method for high-resistivity NdFeB permanent magnetic material, characterized in that: The following steps are involved: (1) preparing an oblong sleeve with a length, width and height of l*m*n and a cover with a length, width and height of l*m*k, and processing a rectangular groove in the sleeve; (2) preparing a magnet bar M with a length, width and height of a*b*d, preparing a diffusion source bar T with a length, width and height of a*c*d, and grinding and polishing the surface; where in millimeters, 10≥a≥3, 10≥b≥3, c≥0.5, d≥3; (3) Alternately assembling the magnet bars and the diffusion source bars into the rectangular slots, covering them with lids, and performing vacuum electron beam welding; (4) subjecting the welded package to hot isostatic pressing to obtain a diffusion multi-element node; (5) cutting the diffusion multi-element node into multiple slices parallel to the long elliptical surface, sealing the tube and performing diffusion heat treatment at different temperatures or times according to subsequent test requirements to obtain multiple groups of high resistivity NdFeB permanent magnet material diffusion multi-element nodes under different heat treatment conditions; (6) Conduct resistivity and magnetic property tests on the interfaces of the obtained NdFeB permanent magnet material diffusion multi-node, and select the interface that meets the required resistivity and magnetic property requirements; prepare NdFeB permanent magnet material based on the component composition on both sides of the interface and the corresponding heat treatment conditions.
2. The method according to claim 1, characterized in that In step (1), the sheath material is one of 304 stainless steel, pure iron, and Cr metal.
3. The method according to claim 1, characterized in that The magnet strip M in step (2) is selected from one or more of NdFeB magnet and NdDyTbFeB magnet, wherein the NdFeB magnet composition is: (Nd x Pr y A z D 1-x-y-z ) a Fe bal M c B e , Nd is the rare earth element neodymium, Pr is the rare earth element praseodymium, A is one or more rare earth elements La, Ce, Y, D is one or more rare earth elements other than Dy, Tb, Nd, Pr, La, Ce, Y, Fe is iron, B is boron, M is one or more elements of Al, Ga, Cu, Ti, Cr, Mn, Mo, Nb, P, Si, Ta, V, Zr, Ni, Co; wherein the composition of NdDyTbFeB magnet is: (Nd x’ Pr y’ R z’ E 1-x’-y’-z’ ) b Fe bal N d B f , R is one or two of the rare earth elements Dy and Tb, E is one or more of the rare earth elements other than Dy, Tb, Nd, Pr, La, Ce, and Y, and N is one or more of the elements selected from the group consisting of Al, Ga, Cu, Ti, Cr, Mn, Mo, Nb, P, Si, Ta, V, Zr, Ni, and Co; calculated in mass percentage, 0.2≤x≤1, 0≤y≤0.5, 0≤z≤0.8, 28.5≤a≤33.5, 0.3≤c≤6, 0.85≤e≤1.5, 0.5≤x'≤1, 0≤y'≤0.4, 0.05≤z'≤0.5, 27≤b≤33.5, 0.2≤d≤6, and 0.85≤f≤1.5 are satisfied.
4. The method according to claim 1, characterized in that The diffusion source T in step (2) is selected from S g Fe bal Q h S t One or more of the following: S is one or more rare earth elements selected from Dy, Tb, Nd, Pr, Gd, and Ho; Fe is iron; Q is one or more elements selected from Al, Ga, Cu, Ni, and Co; S is one or more elements selected from Sn, Si, Zn, Zr, and Pb; and 0.5≤g≤0.8, 0.05≤h≤0.45, and 0.05≤t≤0.45 are satisfied.
5. The method according to claim 1, characterized in that The vacuum degree of the vacuum electron beam welding in step (3) is 5*10 -5 ~5*10 -4 Pa, weld width is 0.5~1.5mm.
6. The method according to claim 1, characterized in that The hot isostatic pressing treatment temperature in step (4) is 650-1000° C., the time is 2-5 hours, and the pressure is 50-300 MPa.
7. The method according to claim 1, characterized in that The tube sealing in step (5) is an argon atmosphere of 0.03-0.06 MPa.
8. The method according to claim 1, characterized in that: The diffusion heat treatment time in step (5) is 2 to 30 days, and the diffusion heat treatment temperature is 800 to 1100°C.
9. The high resistivity NdFeB permanent magnet material prepared by the method according to any one of claims 1 to 8.
Citation Information
Patent Citations
High-flux grain boundary diffusion method of neodymium iron boron rare earth permanent magnet material
CN115346788A
High-coercivity neodymium-iron-boron magnet and preparation method thereof
CN116403824A
Preparation method and application of high-resistivity magnet
CN116978685A
High-throughput preparation method of (Sm, T) (Fe, M) 12-phase alloy based on diffusion of multiple sections
CN117418176A
High-performance double-alloy diffusion neodymium-iron-boron magnet and preparation method thereof
CN118571636A